A medical catheter with a hydrophilic coating on the inner wall and a preparation method thereof
A macromolecular ultraviolet light initiator anchors a hydrophilic coating on medical catheters' inner walls, addressing adherence issues and enhancing stability and durability.
Patent Information
- Application Number
- CN202310326643.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-29
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2043-03-29
AI Technical Summary
Medical catheters, particularly intravascular ones, adhere to proteins and blood cells due to hydrophobic interactions, leading to thrombosis and reduced service life, with existing hydrophilic coatings on outer surfaces being unstable and difficult to apply to the inner walls of narrow catheters.
A method involving a macromolecular ultraviolet light initiator is used to anchor a hydrophilic coating on the inner wall of catheters, forming an ultrathin cross-linked layer through polymerization and ultraviolet curing, enhancing adhesion and stability.
The method results in a hydrophilic coating with improved firmness and wear resistance, reducing protein adsorption and thrombus formation, and extending catheter service life.
Smart Images

Figure CN116370719B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of medical catheters, and in particular to a medical catheter with a hydrophilic coating on its inner wall and a preparation method thereof. Background Art
[0002] Medical catheters are mostly made of hydrophobic materials, such as polyurethane, silicone rubber, polyvinyl chloride, etc., which are prone to adhere to proteins due to hydrophobic-hydrophobic interactions during use, especially intravascular catheters, which are also prone to adhere to platelets and red blood cells, thereby causing thrombosis, which will reduce the service life of the catheter and even cause secondary damage to the patient. Therefore, hydrophilic modification of the catheter surface is very necessary.
[0003] The method of using hydrophilic coating to improve the hydrophilicity of medical devices is already well known. However, during use, the coating is easily detached from the surface due to the weak bonding between the coating and the surface of the polymer material, resulting in unstable and persistent hydrophilic effect.
[0004] Existing hydrophilic modification technologies are mostly applied to the outer surface of catheters, but due to the small inner diameter and narrow space of medical catheters, these technologies are difficult to apply to the inner wall of catheters.
[0005] Therefore, it has become an urgent problem for technicians in this technical field to study a medical catheter with a strong inner wall hydrophilic coating to reduce protein adsorption and thrombus formation and extend the service life of the catheter. Summary of the invention
[0006] The purpose of the present invention is to address the existing problems, and the primary purpose is to provide a method for preparing a medical catheter with a hydrophilic coating on the inner wall. The present invention first applies a macromolecular ultraviolet light initiator solution and a catheter substrate solution to a core rod respectively to obtain a thin-walled catheter embryo, then initiates polymerization of hydrophilic monomers in the catheter embryo to obtain a hydrophilic inner wall coating, and finally the embryo is further dipped in the catheter substrate solution to obtain a medical catheter. The method improves the firmness of the coating by anchoring the macromolecular light initiator molecular chain in the inner wall of the catheter, and further forming an ultrathin cross-linked layer on the inner wall of the catheter through ultraviolet light curing.
[0007] Another object of the present invention is to provide a medical catheter with a hydrophilic coating on its inner wall prepared by the above method.
[0008] The present invention is achieved through the following technical solutions:
[0009] A method for preparing a medical catheter having a hydrophilic coating on its inner wall comprises the following steps:
[0010] (1) Synthesis of polyurethane-based macromolecular ultraviolet photoinitiator (PU2959): Weigh polytetramethylene glycol (PTMG) and hexamethylene diisocyanate (HDI), stir evenly, add a catalyst, add a solvent to reduce the reaction viscosity until the stirring rod blade can fully stir every reactant, perform a first stirring reaction, and obtain an isocyanate-terminated polyurethane solution; dissolve a small molecule ultraviolet photoinitiator in a solvent, and then add it to the isocyanate-terminated polyurethane solution, perform a second stirring reaction, and dry after the reaction to obtain a polyurethane-based macromolecular ultraviolet photoinitiator (PU2959);
[0011] (2) Preparation of catheter embryos: immersing a core rod into a solution containing a polyurethane-based macromolecular photoinitiator, taking out the core rod, air-drying it, and then immersing it into a catheter substrate solution. Repeating the above operation multiple times can obtain a catheter embryo containing a polyurethane-based macromolecular photoinitiator;
[0012] (3) Embryo demoulding: The core rod with the catheter embryo body adhered in step (2) is immersed in a demoulding solution to separate the catheter embryo body from the core rod, and then dried to obtain a catheter embryo body with a UV light initiator on the inner wall.
[0013] (4) grafting the inner wall of the embryo: inserting a small diameter core rod into the catheter embryo obtained in step (3), injecting a mixed aqueous solution containing a hydrophilic olefin monomer and a cross-linking agent into the gap between the embryo and the core rod, and irradiating with ultraviolet light and infrared light to obtain a thin-walled catheter embryo with a hydrophilic coating on the inner wall;
[0014] (5) Thickening the thin-walled catheter embryo: The thin-walled catheter embryo obtained in step (4) is immersed in a catheter base material solution, naturally air-dried, and this step is repeated multiple times to obtain a catheter with a predetermined thickness; then the catheter is rinsed and dried to obtain a medical catheter with a hydrophilic coating on the inner wall.
[0015] Furthermore, in step (1), the uniform stirring refers to stirring at 55 to 75° C. and a rotation speed of 50 to 80 r / min;
[0016] Furthermore, in step (1), the catalyst is one of bismuth neododecanoate, triethylamine, and dibutyltin dilaurate, with a concentration of 0.3 to 0.5 g / ml; preferably bismuth neododecanoate, which is dissolved in anhydrous DMF at a concentration of 0.3 g / ml; the amount of catalyst added is 2 to 5‰ of the total mass of PTMG and HDI.
[0017] Furthermore, in step (1), the solvent is one of anhydrous N,N-dimethylformamide (DMF), anhydrous N,N-dimethylacetamide (DMAc), and anhydrous dioxane;
[0018] Furthermore, in step (1), the first stirring reaction refers to stirring the reaction at 55-65° C. for 4-6 hours;
[0019] Further, in step (1), the small molecule UV initiator is 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone (Irgacure 2959);
[0020] Furthermore, in step (1), the second stirring reaction refers to stirring the reaction at 55-65° C. for 8-12 hours; the washing refers to dropping the reactant solution into a large amount of deionized water to remove the solvent and unreacted small molecule ultraviolet initiator; the drying temperature is 40-60° C.;
[0021] Furthermore, in step (1), the ratio of the amounts of the raw materials is PTMG:HDI:small molecule ultraviolet initiator=9:10:2.5-17:18:2.5;
[0022] Further, in step (1), the molecular weight of the polyurethane-based macromolecular UV initiator (PU2959) is 10,000 to 20,000;
[0023] Furthermore, in step (2), the diameter of the mandrel is 3 to 6 mm;
[0024] Furthermore, in step (2), the solvent of the solution containing the polyurethane-based macromolecular photoinitiator is one of tetrahydrofuran, dioxane, dichloromethane, ethanol, etc., and the solution concentration is 10 to 20 wt.%;
[0025] Furthermore, in step (2), the catheter substrate is polyvinyl chloride (PVC), polyurethane (PU), etc., and the solvent used in the catheter substrate solution is one of tetrahydrofuran, dioxane, dichloromethane, ethanol, etc., and the solution concentration is 10-20wt.%
[0026] Furthermore, in step (2), the thickness of the catheter embryo containing the polyurethane-based macromolecular photoinitiator is 100 to 200 μm;
[0027] Furthermore, in step (3), the demoulding solution is at least one of petroleum ether and dichloromethane; further preferably, the demoulding solution is a mixed solvent of petroleum ether and dichloromethane, and the volume ratio of petroleum ether to dichloromethane is 8:2 to 9:1; the immersion time is 1 to 10 minutes;
[0028] Furthermore, in step (4), the small diameter of the mandrel is 2 to 5 mm;
[0029] Furthermore, in step (4), the hydrophilic olefin monomer comprises at least one of the following types: methacryloylethyl sulfobetaine (SBMA), acrylic acid (AA), acrylamide (AM), vinyl pyrrolidone (VP), and hydroxyethyl methacrylate (HEMA); the concentration of the hydrophilic olefin monomer in water is 10 to 20 wt.%;
[0030] Furthermore, in step (4), the cross-linking agent is a water-soluble cross-linking agent, which is N,N'-methylenebisacrylamide (MBAA), and the concentration in water is 0.5 to 1 wt.%;
[0031] Furthermore, in step (4), an ultraviolet lamp with a wavelength of 365 nm is selected, and an infrared lamp with a wavelength in the mid-infrared region (2.5 to 25 μm) is selected, and the illumination time is 5 to 30 minutes according to the gelation speed;
[0032] Furthermore, in step (5), small molecules with antibacterial and anticoagulant functions may be added to the catheter substrate solution; different embryo materials may be selected according to the functional requirements to prepare a multi-layer composite material tube;
[0033] Further preferably, the antibacterial and anticoagulant functional small molecules are nitric oxide donors: including the following types: S-nitrosothiol (RSNO), organic nitrates, diazeniumdiolate (N-Diazeniumdiolate), etc.;
[0034] Further preferably, the antibacterial and anticoagulant small molecules can be dissolved in the catheter material solution or blended therein, and the concentration can be 5 to 15 wt.%;
[0035] Further, in step (5), the thickness of the conduit is 300 to 600 μm;
[0036] Furthermore, in step (5), the flushing is to flush the catheter with deionized water to remove the uncrosslinked hydrogel and unreacted monomers on the inner wall of the catheter;
[0037] Furthermore, in step (5), the drying refers to drying at 35 to 50° C. for 4 to 12 hours.
[0038] The present invention adopts the above technical solution, and has the following technical effects compared with the prior art:
[0039] (1) Since a macromolecular ultraviolet light initiator is used as the inner wall coating, the molecular chain is long. When the catheter substrate solution is dip-coated, the initiator molecular chain diffuses into the catheter material and entangles with the catheter material molecular chain, playing an anchoring role and enhancing the adhesion of the initiator.
[0040] (2) Since the hydrophilic monomers are polymerized on the surface of the catheter to produce an ultra-thin cross-linked layer, the firmness and wear resistance of the hydrophilic coating are further improved.
[0041] (3) Since ultraviolet light cannot decompose deep-seated initiators due to its weak penetration, mid-infrared light irradiation can quickly heat the material, prompting the effective initiating chain segments of the macromolecular photoinitiator to migrate to the surface, thus providing more grafting points. In addition, infrared light heating can also increase the polymerization rate and shorten the polymerization time.
[0042] (4) Compared with extruded tubes, it is possible to produce thinner-walled tubes and effectively change the composition of the tube wall material. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 The preparation process of the medical catheter with a hydrophilic coating on the inner wall provided by the present invention;
[0044] Figure 2 The water contact angles of the catheter embryos, polyurethane films (PU) and coatings with macromolecular ultraviolet photoinitiator (PU259) prepared in Examples 1 to 3 of the present invention;
[0045] Figure 3 The water contact angle change of the catheter embryo prepared in Example 1;
[0046] Figure 4 The change of friction coefficient of polyurethane film (PU-S) with macromolecular photoinitiator solution spin-coated on the surface and untreated PU film (PU) within 1h test time;
[0047] Figure 5 The surface protein adsorption test of polyurethane film (PU-S) with macromolecular photoinitiator solution spin-coated on the surface and untreated PU film (PU);
[0048] Figure 6 Figure 2 is the antibacterial curve of catheters with different GSNO loading amounts, where A is the antibacterial curve of catheters with different GSNO loading amounts against MRSA, and B is the antibacterial curve of catheters with different GSNO loading amounts against E.coli. DETAILED DESCRIPTION
[0049] The present invention is described in detail and specifically by specific examples below to better understand the present invention, but the following examples do not limit the scope of the present invention. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0050] Figure 1The preparation process of the medical catheter with a hydrophilic coating on the inner wall provided by the present invention is taken as an example of catheter substrate polyurethane, hydrophilic monomer SBMA, and crosslinking agent MBAA. The core rod is dipped in a macromolecular initiator solution and a PU solution, and then the hydrophilic monomer and the crosslinking agent solution are added, and polymerization is initiated under the combined irradiation of 365nm ultraviolet light and infrared light to prepare a hydrophilic cross-linked network coating on the inner wall of the catheter embryo, and then dipped in a PU solution containing S-nitrosoglutathione (GSNO) to form a catheter.
[0051] Example 1
[0052] (1) Synthesis of polyurethane-based macromolecular UV photoinitiator (PU2959): Weigh 5.351 g of PTMG-1000 (from Sigma Aldrich) after dehydration into a three-necked flask, add 1.000 g of HDI (from TCI Chemical), and heat with stirring (60°C, 50 r / min). Add 50 μl of catalyst bismuth neododecanoate solution (bismuth neododecanoate is dissolved in anhydrous DMF, the concentration is 0.3 g / ml, from Sigma Aldrich), and immediately add 10 ml of anhydrous DMF. When the stirring blade cannot fully stir the reactants, add another 10 ml of anhydrous DMF, react at 65°C for 5 hours, and obtain an isocyanate-terminated polyurethane solution. Weigh 333 mg of Irgacure 2959 (from MacLean) and dissolve it in 5 ml of anhydrous DMF, add it to the above reaction solution, and react at 65°C for 8 hours. The reactant solution was dripped into deionized water, stirred, and dried at 50°C to obtain the product polyurethane-based macromolecular ultraviolet photoinitiator (PU2959). The product was 5.76 g, with a yield of 87%.
[0053] (2) Preparation of catheter embryos: The above-synthesized PU2959 was dissolved in tetrahydrofuran to prepare a 20 wt.% solution. A PTFE mandrel with a diameter of 5 mm was immersed in the above solution, taken out and air-dried, and then immersed in a 10 wt.% polyurethane solution. When the liquid on the tube no longer dripped down, it was transferred to a ventilated place to dry naturally, and then immersed in the catheter base material solution. This operation was repeated four times to obtain a catheter embryo containing a polyurethane-based macromolecular photoinitiator with a thickness of approximately 100 μm.
[0054] (3) Embryo demolding: The catheter embryo is immersed in a mixed solution of petroleum ether and dichloromethane with a volume ratio of 9:1. After 5 minutes, the catheter embryo can be separated from the PTFE core rod. It is dried in an oven at 50°C for 1 hour to obtain a catheter embryo with a UV light initiator on the inner wall.
[0055] (4) Grafting on the inner wall of the embryo: Methacryloylethyl sulfobetaine (SBMA) and N,N'-methylenebisacrylamide (MBAA) were dissolved in deionized water, with the concentration of SBMA being 10wt.%, and the concentration of MBAA being 1wt.%. The catheter embryo was placed on a 3mm PTFE mandrel, and the above solution was injected to fill the gap. The embryo was then irradiated under 365nm ultraviolet and infrared light for 20 minutes to obtain a thin-walled catheter embryo with a hydrophilic coating on the inner wall.
[0056] (5) Thickening of the thin-walled catheter embryo with a hydrophilic coating on the inner wall: The catheter embryo obtained above was immersed in a polyurethane solution, naturally air-dried, and this step was repeated multiple times to reach a thickness of 500 μm. The prepared catheter was rinsed with deionized water to remove the uncrosslinked hydrogel and unreacted monomers on the inner wall of the catheter. Drying at 50°C for 8 hours, a medical catheter with a hydrophilic coating on the inner wall was obtained.
[0057] Example 2
[0058] (1) Synthesis of polyurethane-based macromolecular ultraviolet photoinitiator (PU2959): Weigh 5.615 g of PTMG-1000 after dehydration into a three-necked flask, add 1.000 g of HDI, and heat with stirring (60°C, 50 r / min). Add 50 μl of catalyst bismuth neodecanoate solution (bismuth neodecanoate is dissolved in anhydrous DMF, with a concentration of 0.3 g / ml), and immediately add 10 ml of anhydrous DMF. When the stirring blade cannot fully stir the reactant, add another 10 ml of anhydrous DMF, and react at 55°C for 6 hours to obtain an isocyanate-terminated polyurethane solution. Weigh 185 mg of Irgacure 2959, dissolve it in 5 ml of anhydrous DMF, add it to the above reaction solution, and react at 60°C for 12 hours. The reactant solution is dripped into deionized water, stirred, and dried at 50°C to obtain the product polyurethane-based macromolecular ultraviolet photoinitiator (PU2959). Product: 5.54 g, yield: 83.7%.
[0059] (2) Preparation of catheter embryos: The above-synthesized PU2959 was dissolved in tetrahydrofuran to prepare a 10 wt.% solution. A PTFE mandrel with a diameter of 5 mm was immersed in the above solution, taken out and air-dried, and then immersed in a 15 wt.% polyurethane solution, taken out and air-dried. This operation was repeated four times to obtain a catheter embryo with a thickness of about 200 μm.
[0060] (3) Embryo demolding: The catheter embryo is immersed in a mixed solution of petroleum ether and dichloromethane with a volume ratio of 8:2. After 3 minutes, the catheter embryo can be separated from the PTFE core rod. It is dried in an oven at 50°C for 1 hour to obtain a catheter embryo with a UV light initiator on the inner wall.
[0061] (4) Grafting on the inner wall of the embryo: Methacryloylethyl sulfobetaine (SBMA) and N,N'-methylenebisacrylamide (MBAA) were dissolved in deionized water, with the concentration of SBMA being 10wt.%, and the concentration of MBAA being 1wt.%. The catheter embryo was placed on a 3mm PTFE mandrel, the above solution was injected, and then irradiated under 365nm ultraviolet and infrared light for 30 minutes to form a gel, thereby obtaining a catheter embryo with a hydrophilic coating on the inner wall.
[0062] (5) Thickening of the thin-walled catheter embryo with a hydrophilic coating on the inner wall: The catheter embryo obtained above was immersed in a polyurethane solution, naturally air-dried, and this step was repeated multiple times to reach a thickness of 500 μm. The prepared catheter was rinsed with deionized water to remove the uncrosslinked hydrogel and unreacted monomers on the inner wall of the catheter. Drying at 50°C for 8 hours, a medical catheter with a hydrophilic coating on the inner wall was obtained.
[0063] Example 3
[0064] (1) Synthesis of polyurethane-based macromolecular ultraviolet photoinitiator (PU2959): Weigh 5.351 g of PTMG-1000 after dehydration into a three-necked flask, add 1.000 g of HDI, and heat with stirring (65°C, 50 r / min). Add 50 μl of catalyst bismuth neodecanoate solution (bismuth neodecanoate is dissolved in anhydrous DMF, the concentration is 0.3 g / ml), immediately add 10 ml of anhydrous DMF, when the stirring blade cannot fully stir the reactant, add another 10 ml of anhydrous DMF, and react at 60°C for 5 hours. Weigh 333 mg of Irgacure2959, dissolve it in 5 ml of anhydrous DMF, add it to the above reaction solution, and react at 60°C for 8 hours. The reactant solution is dripped into deionized water, stirred, and dried at 50°C to obtain the product polyurethane-based macromolecular ultraviolet photoinitiator (PU2959). The product is 5.56 g, with a yield of 84%.
[0065] (2) Preparation of catheter embryos: The above-synthesized PU2959 was dissolved in tetrahydrofuran to prepare a 15 wt.% solution. A PTFE mandrel with a diameter of 5 mm was immersed in the above solution, taken out and air-dried, and then immersed in a 10 wt.% polyurethane solution, taken out and air-dried, and this operation was repeated four times to obtain a catheter embryo with a thickness of 100 μm.
[0066] (3) Embryo demolding: The catheter embryo is immersed in a mixed solution of petroleum ether and dichloromethane with a volume ratio of 9:1. After 5 minutes, the catheter embryo can be separated from the PTFE core rod. It is dried in an oven at 50°C for 1 hour to obtain a catheter embryo with a UV light initiator on the inner wall.
[0067] (4) Inner wall grafting: acrylic acid (AA) and N,N'-methylenebisacrylamide (MBAA) were dissolved in deionized water, with an AA concentration of 20 wt.% and an MBAA concentration of 0.5 wt.%. The catheter embryo was placed on a 3 mm PTFE mandrel, the above solution was injected, and then irradiated under 365 nm ultraviolet and infrared light for 30 minutes to form a gel, thereby obtaining a catheter embryo with a hydrophilic coating on the inner wall.
[0068] (5) Thickening of the thin-walled catheter embryo with a hydrophilic coating on the inner wall: The catheter embryo obtained above was immersed in a polyurethane solution, naturally air-dried, and this step was repeated multiple times to reach a thickness of 500 μm. The prepared catheter was rinsed with deionized water to remove the uncrosslinked hydrogel and unreacted monomers on the inner wall of the catheter. Drying at 50°C for 8 hours, a medical catheter with a hydrophilic coating on the inner wall was obtained.
[0069] Example 4
[0070] (1) Synthesis of polyurethane-based macromolecular ultraviolet photoinitiator (PU2959): Weigh 5.615g of PTMG-1000 after dehydration into a three-necked flask, add 1.000g of HDI, and heat with stirring (60°C, 50r / min). Add 50μl of catalyst bismuth neodecanoate solution (bismuth neodecanoate is dissolved in anhydrous DMF, the concentration is 0.3g / ml), immediately add 10ml of anhydrous DMF, when the stirring blade cannot fully stir the reactant, add another 10ml of anhydrous DMF, and react at 60°C for 6 hours. Weigh 185mg of Irgacure2959 and dissolve it in 5ml of anhydrous DMF, add it to the above reaction solution, and react at 65°C for 12 hours. Drop the reactant solution into deionized water, stir, and dry at 50°C. The product is 5.54g, with a yield of 83.7%.
[0071] (2) Preparation of catheter embryos: The above-synthesized PU2959 was dissolved in tetrahydrofuran to prepare a 15 wt.% solution. A PTFE mandrel with a diameter of 5 mm was immersed in the above solution, taken out and air-dried, and then immersed in a 10 wt.% polyurethane solution, taken out and air-dried. This operation was repeated four times to obtain a catheter embryo with a thickness of 150 μm.
[0072] (3) Embryo demolding: The catheter embryo is immersed in a mixed solution of petroleum ether and dichloromethane with a volume ratio of 9:1. After 5 minutes, the catheter embryo can be separated from the PTFE core rod. It is dried in an oven at 50°C for 1 hour to obtain a catheter embryo with a UV light initiator on the inner wall.
[0073] (4) Grafting on the inner wall of the embryo: Methacryloylethyl sulfobetaine (SBMA) and N,N'-methylenebisacrylamide (MBAA) were dissolved in deionized water, with the concentration of SBMA being 10wt.%, and the concentration of MBAA being 1wt.%. The catheter embryo was placed on a 3mm PTFE mandrel, and the above solution was injected to fill the gap. The embryo was then irradiated with 365nm ultraviolet light and infrared light for 20 minutes to obtain a thin-walled catheter embryo with a hydrophilic coating on the inner wall.
[0074] (5) Thickening of thin-walled catheter embryos with hydrophilic coating on the inner wall: Grind nitrosoglutathione (GSNO) into fine powder, add it to the polyurethane solution, shake and stir to obtain GSNO / PU suspension, so that the mass ratio of GSNO to PU in the suspension is 5:95, 10:90, and 15:85, respectively. Immerse the catheter embryos obtained above in different GSNO / PU suspensions, dry them, and repeat this step several times to reach a thickness of 500 μm. Rinse the prepared catheter with deionized water to remove the uncrosslinked hydrogel and unreacted monomers on the inner wall of the catheter. Dry at 37°C for 12 hours to obtain an antibacterial and anticoagulant medical catheter with a hydrophilic coating on the inner wall.
[0075] Experiment 1: Catheter inner wall water contact test:
[0076] (1) Experimental purpose:
[0077] The hydrophilicity of the inner wall of the catheter was tested by water contact angle.
[0078] (2) Experimental methods:
[0079] The catheter embryos in Examples 1 to 3 were cut open, cleaned, and the uncrosslinked hydrogel on the surface was removed, and the embryos were attached to a glass slide with double-sided tape, and the contact angle of the inner wall of the catheter was measured using a contact angle tester. After taking pictures, the contact angle was analyzed using Image J.
[0080] The same method was used to test the surface water contact angle of a polyurethane film (marked as PU) and a polyurethane film containing a macromolecular UV photoinitiator coating (marked as PU2959) for comparison.
[0081] The preparation method of the polyurethane membrane (marked as PU) is as follows: immerse a PTFE core rod with a diameter of 5 mm into a 10wt.% polyurethane solution, take it out and air-dry it, repeat this operation four times to obtain a polyurethane catheter (PU catheter) with a thickness of 150 μm, cut it open, and obtain the polyurethane membrane.
[0082] Preparation method of polyurethane film containing macromolecular ultraviolet photoinitiator coating (labeled as PU2959): the thin-walled catheter is prepared in the same way as in Example 1, and then cut open to obtain polyurethane film containing macromolecular ultraviolet photoinitiator coating.
[0083] (3) Experimental results:
[0084] Figure 2 The water contact angles of the catheter embryos, polyurethane films (PU) and macromolecular ultraviolet photoinitiator coatings (PU2959) prepared in Examples 1 to 3 of the present invention; Figure 2 In the test results, the water contact angles of Examples 1 to 3 are 10°, 12°, and 34°, respectively. Compared with polyurethane, the hydrophilic coating prepared by this method greatly improves the hydrophilicity of the material surface, especially the introduction of zwitterionic SBMA, which makes the coating have a super-hydrophilic effect.
[0085] Figure 3 The water contact angle of the catheter embryo prepared in Example 1 changes. When the water droplet first touches the material, the contact angle is 42.3°. After 1 second, the water contact angle decreases to 13°. Figure 3 It can be seen from the test results that water droplets spread rapidly on the hydrophilic coating. The water contact angle is 13° after 1 second and only 10° after stabilization, which has a super hydrophilic effect.
[0086] (4) Experimental conclusion:
[0087] The above water contact angle test results show that the catheter inner wall coating prepared by this method has very excellent hydrophilicity, and the hydrophilic network coating prepared with zwitterionic SBMA as a monomer can even achieve a super hydrophilic effect.
[0088] Experiment 2: Coating lubrication performance and stability performance test:
[0089] (1) Experimental purpose:
[0090] The lubrication performance and stability of the coating were characterized by measuring the change in the friction coefficient of the catheter.
[0091] (2) Experimental methods:
[0092] A PU2959 solution with a concentration of 15wt.% was spin-coated on the surface of a polyurethane film (PU film, the preparation method of which was consistent with that in Experiment 1) (diameter 15mm, thickness 150μm), and after drying, it was placed in a 24-well plate, and then 500μl of SBMA solution (wherein the concentration of SBMA was 10wt.%, and the concentration of MBAA was 1wt.%) was added, and ultraviolet light and infrared light were irradiated for 30 minutes in total, and the polyurethane film was taken out, the surface was cleaned, and it was naturally dried for use (named PU-S). The untreated PU film (named PU) and the PU-S film were stuck in a culture dish, PBS buffer (brand: Gibco) was added and soaked, and the surface of the material was reciprocated by friction wear and mechanical properties tester to detect the change of the material friction coefficient.
[0093] The experimental parameters are as follows: the carrier is a steel ball with a diameter of 8 mm, the load is 2 N, the sliding rate is 1 mm / s, the sliding distance is 5 mm, and the test time is 1 h.
[0094] (3) Experimental results:
[0095] Figure 4 The change of friction coefficient of polyurethane film (PU-S) with macromolecular photoinitiator solution spin-coated on the surface and untreated PU film (PU) within 1h test time; Figure 4 It can be seen that the friction coefficient of the PU film reaches 0.17 after stabilization, and then suddenly increases at around 2270s. It should be that the wear of the material causes the friction force to increase, reaching about 0.18, and then slowly decreases. The friction coefficient of the PU-S film reached 0.22 at the beginning, and then decreased rapidly, and was 0.13 after stabilization. It should be the process of static friction on the surface of the material turning into sliding friction. After that, a hydration layer was formed on the surface of the material, which improved the lubrication performance, and the friction coefficient decreased after stabilization. Compared with the control example, the friction coefficient of the embodiment decreased by 23.5%. In addition, the coating did not show obvious wear in the 1h reciprocating friction test.
[0096] (4) Experimental conclusion:
[0097] The zwitterionic hydrophilic coating on the surface of the material can effectively reduce the friction coefficient of the material and improve the lubricity of the material. In addition, the coating has strong adhesion and good wear resistance.
[0098] Experiment 3: Material anti-protein adsorption test:
[0099] (1) Experimental purpose:
[0100] The anti-protein adhesion properties of the material were characterized by protein adsorption experiments.
[0101] (2) Experimental methods:
[0102] A PTFE core rod with a diameter of 5 mm was immersed in a 10 wt.% polyurethane solution, taken out, air-dried, and repeated 15 times. The solution was then dried at 50°C to obtain a polyurethane catheter with a thickness of approximately 500 μm as a control example.
[0103] Cut the medical catheters prepared in the control example and Examples 1 to 3 with a length of 5 mm respectively, place them vertically in a 48-well plate, add 1 ml of 1 wt.% bovine serum albumin (BSA) solution to each well, and incubate at 37°C for 2 hours. Take out the catheter, wash the surface of the material gently with PBS, then add 1 ml of SDS washing solution (2 wt.% sodium dodecyl sulfate (SDS) + 0.05 M NaOH) and ultrasonically vibrate for 30 minutes to remove the protein adsorbed on the membrane, then take 20 μl and measure the protein concentration by BCA protein detection kit (Biyuntian Biotechnology).
[0104] (3) Experimental results:
[0105] Figure 5 For the control example and the catheter surface protein adsorption test in Examples 1 to 3: Figure 5 From the experimental results, it can be seen that the protein adsorption amount of the control example is 10.26±0.32μg, and that of Examples 1 to 3 are 6.48±0.20μg, 6.13±0.62μg, and 7.99±0.80μg, respectively.
[0106] (4) Experimental conclusion
[0107] The medical catheters with a hydrophilic coating on the inner wall prepared in Examples 1 to 3 can effectively inhibit the adsorption of proteins.
[0108] Experiment 4: Catheter antibacterial performance test:
[0109] (1) Experimental purpose:
[0110] The antibacterial property of the catheter was characterized by measuring the antibacterial curve of the catheter.
[0111] (2) Experimental methods:
[0112] Take several 15 ml centrifuge tubes, add 7 ml LB broth (Huankai Microbiology 028320) to each centrifuge tube, and then add 100 μl 10 6 CFU / ml of methicillin-resistant Staphylococcus aureus (MRSA) and Escherichia coli (E. coli). 500 mg of different catheters (named G5, G10, G15, respectively) with a mass ratio of GSNO to PU of 5:95, 10:90, and 15:85 in Example 4 were cut and placed in the above centrifuge tubes. In addition, 500 mg of PU catheters without GSNO (PU catheters prepared in Experiment 1, named G0) were added as a control group. Only equal volumes of broth and bacterial solution were added as a blank control group (recorded as Blank).
[0113] After incubation at 220 rpm in a 37°C constant temperature shaker for 6, 12, 24, 36, 48, 60 and 72 h, 100 μl of the bacterial suspension was placed in a 96-well plate, and the absorbance of the culture solution at a wavelength of 600 nm was measured using an enzyme-labeled instrument.
[0114] Antibacterial rate calculation formula:
[0115]
[0116] (3) Experimental results:
[0117] Figure 6 Figure 2 is the antibacterial curve of catheters with different GSNO loading amounts, where A is the antibacterial curve of catheters with different GSNO loading amounts against MRSA, and B is the antibacterial curve of catheters with different GSNO loading amounts against E.coli.
[0118] from Figure 6 It can be seen that the more GSNO content in the catheter, the better the antibacterial effect of the catheter, and the antibacterial effect of the catheter on MRSA is better than that on E.coli. Figure 6 In A, at 6-12h, the bacteria are in the logarithmic growth phase with a fast growth rate. The NO released by G5 and G10 in the early stage is insufficient, so the inhibition rate is reduced. On the contrary, the NO released by G15 is sufficient to inhibit bacterial growth, so the inhibition rate is still increased. At 24-72h, the NO released by G5 is not enough to inhibit the growth of MRSA, so the inhibition rate has been decreasing. Figure 6 In Figure B, in particular, the antibacterial rate of G15 also decreased at 6-12h, which may be because E. coli grows faster than MRSA. Combining Figures A and B, it can be clearly seen that the catheter has a better antibacterial effect on MRSA than E. coli. The main reason for this difference may be the different membrane structures of the two. The MRSA cell membrane is a porous structure, while the E. coli cell membrane is a dense structure that is difficult to damage. At 72h, the antibacterial rate of G15 catheter against MRSA reached more than 95%, and the antibacterial rate against E. coli reached more than 65%.
[0119] (4) Experimental conclusion
[0120] The above antibacterial curve results show that the antibacterial catheter with a hydrophilic coating on the inner wall prepared by this method has a good antibacterial effect. When the content of GSNO in the catheter reaches 15wt.%, on the third day, the antibacterial rate of the catheter against MRSA reaches more than 95%, and the antibacterial rate against E.coli reaches more than 65%.
[0121] The specific embodiments of the present invention are described in detail above, but they are only examples, and the present invention is not limited to the specific embodiments described above. For those skilled in the art, any equivalent modifications and substitutions made to the present invention are also within the scope of the present invention. Therefore, the equalization changes and modifications made without departing from the spirit and scope of the present invention should be included in the scope of the present invention.
Claims
1. A method for preparing a medical catheter having a hydrophilic coating on the inner wall, characterized in that: The steps include: (1) Preparation of catheter embryos: immersing a core rod into a solution containing a UV photoinitiator, taking out the core rod, air-drying it, and then immersing it into a catheter substrate solution, repeating the above operation multiple times to obtain a catheter embryo containing a UV photoinitiator; The ultraviolet light initiator is a polyurethane-based macromolecular ultraviolet light initiator, and its synthesis method comprises the following steps: weighing polybutylene glycol and hexamethylene diisocyanate, stirring evenly, adding a catalyst, adding a solvent to reduce the viscosity of the reactants, and performing a first stirring reaction to obtain an isocyanate-terminated polyurethane solution; dissolving a small molecule ultraviolet light initiator in a solvent, and then adding the solution to the isocyanate-terminated polyurethane solution, performing a second stirring reaction, and drying after the reaction to obtain a polyurethane-based macromolecular ultraviolet light initiator; The small molecule ultraviolet light initiator is 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone; the ratio of the amount of each raw material is polybutylene glycol: hexamethylene diisocyanate: small molecule ultraviolet light initiator = 9:10:2.5~17:18:2.5; The diameter of the mandrel is 3-6 mm; The solvent of the solution containing the ultraviolet light initiator is one of tetrahydrofuran and dioxane, and the concentration of the solution is 10-20 wt.%; The catheter substrate is polyurethane, and the solvent used in the catheter substrate solution is one of tetrahydrofuran and dioxane, and the solution concentration is 10-20 wt.%; The thickness of the catheter embryo containing the ultraviolet light initiator is 100-200 μm; (2) Embryo demolding: immersing the core rod to which the catheter embryo body is attached in step (1) into a demolding solution, separating the catheter embryo body from the core rod, and drying the core rod to obtain a catheter embryo body with a UV light initiator on the inner wall; (3) grafting the inner wall of the embryo: inserting a small diameter core rod into the catheter embryo obtained in step (2), injecting a mixed aqueous solution containing a hydrophilic olefin monomer and a cross-linking agent into the gap between the embryo and the core rod, and irradiating with ultraviolet light and infrared light to obtain a thin-walled catheter embryo with a hydrophilic coating on the inner wall; The small diameter of the mandrel is 2-5 mm; The hydrophilic olefin monomer is methacryloylethyl sulfobetaine; the concentration of the hydrophilic olefin monomer in water is 10-20wt.%; The cross-linking agent is N,N'-methylenebisacrylamide, and the concentration in water is 0.5-1wt.%; Use ultraviolet lamp with wavelength of 365nm and infrared lamp with wavelength of 2.5-25μm in mid-infrared region. According to the gelling speed, the illumination time is 5-30 minutes. (4) Thickening the thin-walled catheter embryo: immersing the thin-walled catheter embryo obtained in step (3) in a catheter base material solution, allowing it to air dry naturally, and repeating this step multiple times to obtain a catheter with a thickness of 300-600 μm; then, the catheter is rinsed and dried to obtain a medical catheter with a hydrophilic coating on the inner wall; The catheter substrate solution is added with small molecules with antibacterial and anticoagulant functions; The antibacterial and anticoagulant small molecule is one of S-nitrosothiol, organic nitrate, and diazeniumdiolate; the antibacterial and anticoagulant small molecule is dissolved in the catheter base material solution, or blended in the catheter base material solution at a concentration of 5-15wt.%.
2. A method for preparing a medical catheter having a hydrophilic coating on the inner wall according to claim 1, characterized in that: The catalyst is one of bismuth neododecanoate, triethylamine, and dibutyltin dilaurate, and the concentration is 0.3-0.5 g / ml; The solvent is one of anhydrous N,N-dimethylformamide, anhydrous N,N-dimethylacetamide, and anhydrous dioxane; The first stirring reaction refers to stirring the reaction at 55-65° C. for 4-6 hours.
3. A method for preparing a medical catheter having a hydrophilic coating on the inner wall according to claim 1, characterized in that: The second stirring reaction refers to stirring the reaction at 55-65°C for 8-12 hours; the drying temperature is 40-60°C.
4. A method for preparing a medical catheter having a hydrophilic coating on the inner wall according to claim 1, characterized in that: The molecular weight of the polyurethane-based macromolecular ultraviolet photoinitiator is 10,000 to 20,000.
5. A method for preparing a medical catheter having a hydrophilic coating on the inner wall according to claim 1, characterized in that: In step (2), the demoulding solution is at least one of petroleum ether and dichloromethane; and the immersion time is 1 to 10 minutes.
6. A method for preparing a medical catheter having a hydrophilic coating on the inner wall according to claim 1, characterized in that: In step (4), the drying refers to drying at 35-50°C for 4-12 hours.
7. A medical catheter with a hydrophilic coating on the inner wall prepared by the method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Completely degradable polymer medicine elution stent and preparation method thereof
CN102210616A
Methacrylate copolymers for medical devices
US20060067908A1
Central venous catheter, preparation method therefor and medical device comprising same
US20220040384A1
Cited By
A silicone rubber-polyurethane composite medical drainage catheter and a preparation method thereof
CN122721682A